Epidemic of Genotype GII.2 Noroviruses during Spring 2004 in Osaka City, Japan - Iritani, Nobuhiro (American Society for Microbiology (ASM), 2008)
Between March and May 2004, a GII.2 genotype norovirus strain caused an epidemic of acute gastroenteritis in Osaka, Japan. Phylogenetic analysis showed that this strain was distinct from all other GII.2 strains detected in Osaka City between April 1996 and March 2005.